Towards a decision-aware declarative process modeling language for knowledge-intensive processes. (30th November 2017) - Mertens, Steven; Gailly, Frederik; Poels, Geert
Highlights: Knowledge-intensive and loosely framed processes require a new modeling approach. Modeling flexibility and knowledge is essential. The approach needs a functional, control-flow, data and resource perspective. The metamodel for a new mixed-perspective modeling approach is proposed. The language-domain appropriateness was validated by process experts. Abstract: Modeling loosely framed and knowledge-intensive business processes with the currently available process modeling languages is very challenging. Some lack the flexibility to model this type of processes, while others are missing one or more perspectives needed to add the necessary level of detail to the models. In this paper we have composed a list of requirements that a modeling language should fulfil in order to adequately support the modeling of this type of processes. Based on these requirements, a metamodel for a new modeling language was developed that satisfies them all. The new language, called DeciClare, incorporates parts of several existing modeling languages, integrating them with new solutions to requirements that had not yet been met. Deciclare is a declarative modeling language at its core, and therefore, can inherently deal with the flexibility required to model loosely framed processes. The complementary resource and data perspectives add the capability to reason about, respectively, resources and data values. The latter makes it possible to encapsulate the knowledge that governs the process flow by offering support for decision modeling. The abstract syntax of DeciClare has been implemented in the form of an Ecore model. Based on this implementation, the language-domain appropriateness of the language was validated by domain experts using the arm fracture case as application scenario.